2021
DOI: 10.1007/s00705-021-05200-0
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of canine parvovirus 2b in Japan: an epidemiological study during 2014-2019

Abstract: Canine parvovirus-2 (CPV-2) is an important pathogen of domestic dogs and wild canids. In Japan, CPV-2 infection remains one of the most common infection diseases among dogs. We analyzed samples collected between 2014 and 2019 to determine the antigenic variants of CPV-2 among dogs in Japan. Our results demonstrated that the CPV-2b variant was predominant. The CPV-2c variant was not found among our samples. Our ndings demonstrate that the distribution of CPV-2 antigenic variants in Japan was more similar to th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…An epidemiological assessment of CPV in Japan in recent years revealed that the CPV-2b variant was dominant from 2014 to 2019. Japan, as an Asian country, was far from Australia, but the variance of CPV was similar [ 25 ]. This indicated a global trend in CPV evolution and prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…An epidemiological assessment of CPV in Japan in recent years revealed that the CPV-2b variant was dominant from 2014 to 2019. Japan, as an Asian country, was far from Australia, but the variance of CPV was similar [ 25 ]. This indicated a global trend in CPV evolution and prevalence.…”
Section: Discussionmentioning
confidence: 99%
“…The rising prevalence rate of CPV has increased the significance of research on CPV subtypes in dogs in recent years. In contrast to the Taiwan (Chiang et al, 2016), Japan (Takano et al, 2021), Brazil (Silva et al, 2022), Germany (Decaro et al, 2007), United States (Kapil et al, 2007) and Australia (Clark et al, 2018), which have a high prevalence of CPV type 2b, Italy (Battilani et al, 2019), Colombia (Galvis et al, 2022), Korea (Yang et al, 2010) and India (Chinchkar et al, 2006) are mostly affected by CPV type 2a (Hirayama et al, 2005). Currently, a third subtype of CPV called CPV type 2c has been documented in several countries.…”
Section: F I G U R Ementioning
confidence: 99%
“…In North and South America, except in Colombia and Canada, CPV-2c is the most common variant. Most countries in Asia, Europe, and Oceania have the CPV-2a variant dominantly distributed, except Japan, Australia, and New Zealand where the CPV-2b variant is prevailing [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%